PERLINDUNGAN HUKUM TERHADAP MASALAH KEBOCORAN DATA NASABAH DIKAITKAN DENGAN PRINSIP KERAHASIAAN BANK - Beryl Nahdah Gunardi, Beryl (2022)
In the implementation of its activities, secrecy principle is an important and upheld principle which underlying the contractual relationship that occurs between bank and its customer. The emergence of legal problems such as costumer data leaking which still happening today can lead to massive loss of trust from its bank customer. The existence of a financial institution, bank, depends on the absolute trust of its customer which is assessed through the bank's compliance with the implementation of its bank secrecy obligations. The loss of the existence from a bank can cause the bank to collapse and in turn giving a domino effect to the country in the form of financial and payment system activities disturbance. This research uses a normative juridical research method that evaluates a primary and secondary legal materials, and also use an empirical juridical method such as interview. Based on the result of the research, it is known that the provisions of bank secrecy are on the law No. 7 of 1992 which is now amended by Law No. 10 of 1998 that concern of a banking matters is considered to have not been effective in resolving the problem of leakage of its costumer data, especially with legal problem that continue to develop. Criminal act of banking such as crime of leaking its customer data secrecy, until now occured through a way that increasingly develope and more unique by hacking the company's network system. It can be said that Indonesia need the urgency of a regulations that explicitly regulate the protection of personal data and also need a sanctions that can apply if there is an event of costumer data secrecy leaking that carried out by criminal mind hackers. Keywords: Legal Protection, Costumer Data Leak, Secrecy Bank Principle.